Abstract Writing: English-Speaking Countries vs. Greece - Sidiropoulou, Maria (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractCross-cultural variation in written discourse has attracted less attention than similar variation in oral communication, although such studies are useful in quite a few areas of application, especially translation. The article intends to investigate tendencies in abstract writing between researchers from English-speaking countries and Greece. The data come from the Proceedings of the 9th World Congress of Applied Linguistics held at Thessaloniki-Halkidiki, Greece, in April 1990. Abstracts by Greek researchers are mostly written in English; it is assumed that internalized mother tongue preferences by Greek will be reflected in their writing in English. A sample of 100 abstracts is examined with respect to the authors' intentions in writing them and their attitude towards the readership. The frameworks assumed are B. Grosz and C. Sidner's theory of discourse structure (1985), P. Brown and S. Levinson's interactional model (1987) and B. Hatim and I. Mason's approach to translation (1990). The differences are of a pragmatic and communicative type: the two research groups differ in their preferences concerning the selection of discourse segments in the abstracts whereas their attitude towards the readership is described by a different positive/negative politeness pattern; no cultural group appears purely positively or negatively polite. Awareness of preferences in abstract writing facilitates both researchers and translators in achieving communicative and pragmatic equivalence in the target language.